СЕРВІС CITED-BY ВІД CROSSREF, DIMENSIONS, ПІДРАХУНОК ЦИТУВАНЬ - Городжа, Л.В. (Інститут електродинаміки НАН України, Київ, 2019)
The possibilities of using DOI digital identifiers for scientific publications and the Cited-by Crosstraf service are considered in the article. Their use is aimed at facilitating the search for information in the electronic array of scientific content and tracked citation of scientific works. References 5, figures 4.